Association Between Access to Oral Health Information and Use of Fluoride Toothpaste with at Least 1000 PPM in Peruvian Children - Oh-Aguilar, Eunji (2026)
Oral health education is assumed to improve knowledge and behaviors regarding fluoride toothpaste use. However, dental caries prevention requires comprehensive strategies that integrate dental examinations, provision of fluoride toothpaste, and preventive treatments.To analyze the association between access to oral health information and the use of fluoride toothpaste with a concentration of ≥1000 ppm in Peruvian children under 12 years of age. A cross-sectional analysis was conducted using nationally representative 2023 ENDES data, including 23,613 children. Independent variables were access to oral health information and its provider; the dependent variable was fluoride toothpaste use (≥1000 ppm). Covariates included wealth index, natural region, health insurance, altitude, area and place of residence, age, and sex. Multilevel Poisson regression estimated prevalence ratios (PR) and 95% confidence intervals (CI).In bivariate analyses, appropriate fluoride toothpaste use was significantly associated with information provider (p<0.001), natural region (p<0.001), altitude (p<0.001), wealth index (p<0.001), age (p<0.001), area (p=0.030), and place of residence (p=0.041). Children living in the coastal region, at lower altitudes, from wealthier households, and older age groups had higher prevalence of use. However, in multivariate analysis, access to oral health information was not significantly associated with appropriate fluoride toothpaste use (coef.: –0.01; PR: 1.00; 95% CI: 0.97–1.04; p=0.808). Access to oral health information was not linked to fluoride toothpaste use ≥1000 ppm among Peruvian children under 12 years, while geographic and socioeconomic factors played a significant role. Educational strategies alone may be inadequate without tackling structural barriers. Strengthening regulations, aligning policies with clinical guidelines, and ensuring equitable access are crucial. This first 2023 ENDES-based analysis offers valuable national evidence to guide targeted interventions and oral health policy.